Patient Satisfaction with Dental and Oral Health Services at Regional Special Hospital of Dental and Oral, South Sulawesi - Johnny Angki; Asriawal Asriawal; Muhammad Saleh; Sainuddin Sainuddin; Bahtiar Bahtiar (Alliance oh Health Activists (AloHA), 2024)
Quality health services are services that can provide satisfaction to customers or patients. This study aims to analyze the quality of dental and oral health services at RSKDGM, South Sulawesi. This descriptive study involving 100 patients at the RSKDGM South Sulawesi Province, from September to November 2021. The research variables were the quality of service which consisted of: tangible, reliability, responsiveness, assurance and empathy; and patient satisfaction. Data were collected through filling out questionnaires, then checked for accuracy and completeness, followed by tabulation, then descriptive data analysis was carried out in the form of minimum, maximum, range, mean and standard deviation. The results showed that the mean score for service quality was good, namely: tangible = 25.50, reliability = 21.74, assurance = 17.33, empathy = 13.23 and responsiveness = 13.17. While the mean score of satisfaction level is 16.81. Furthermore, it is concluded that patients are satisfied with the services provided by RSKDGM, with tangible as the dimension that is felt to be of the highest quality. Keywords: dental and oral health; service quality; satisfaction; tangible